2021
DOI: 10.21203/rs.3.rs-844345/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Innovative Prognostic Symbol Based on Autophagy-Related Long Noncoding RNAs Signature Predicts in Low-Grade Glioma

Abstract: Autophagy is a highly conserved lysosomal degradation process essential in tumorigenesis. However, the involvement of autophagy-related lncRNA in low-grade gliomas (LGG) remains a pending question. Efforts were made to establish an autophagy-related lncRNA signature prognostic in LGG patients, and to explore the behind potential function. We used Univariate Cox, Least Absolute Shrinkage and Selection Operator (Lasso), and Multivariate Cox regression models were designed to establish an autophagy-related lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Many studies have shown the critical role of m 7 G in cancer development, mainly focusing on the regulation of tumor cell genesis and progression, but few investigations on cancer prognosis (Orellana et al, 2021;Rong et al, 2021;Xia et al, 2021). Several studies have recently emerged by constructing mRNA and lncRNA predictive signatures associated with glioma autophagy, pyrogenesis, m 6 A, and ferrogenesis can be used to predict the prognosis of glioma patients (Maimaiti et al, 2022) (Zhou et al, 2021a (Guan et al, 2021) (Shi et al, 2022). However, the study of prognostic m7Grelated lncRNAs in glioma has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown the critical role of m 7 G in cancer development, mainly focusing on the regulation of tumor cell genesis and progression, but few investigations on cancer prognosis (Orellana et al, 2021;Rong et al, 2021;Xia et al, 2021). Several studies have recently emerged by constructing mRNA and lncRNA predictive signatures associated with glioma autophagy, pyrogenesis, m 6 A, and ferrogenesis can be used to predict the prognosis of glioma patients (Maimaiti et al, 2022) (Zhou et al, 2021a (Guan et al, 2021) (Shi et al, 2022). However, the study of prognostic m7Grelated lncRNAs in glioma has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…SNAI3-AS1, an m 7 G prognosis-associated lncRNA, is an important tumor modifier in hepatocellular carcinoma tumor progression (Li et al, 2020). Recently, it has been reported that autophagy-related lncRNA features can accurately predict the prognosis of glioma patients (Maimaiti et al, 2022). Ferroptosisassociated lncRNAs can also predict the prognosis of glioma patients (Shi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%